TEKNIK NON TES: Telaah atas Fungsi Wawancara dan Kuesioner dalam Evaluasi Pendidikan - Sitti Mania (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2008)
Evaluation in the world education constitutes an absolute activity, because, evaluation of the development students learning achievement, evaluation subject can be read. Besides that, through evaluation-teacher, lecturer, and manager who involve in a educational institution can know how far and big are the development and growth of teaching program that held in order to achieve the goal which is formulated. The evaluation can be done by using test technique and non test one.non test technique is very various, but this writing only explains two kinds namely; interview and questionnaire.